EFFICIENCY OF PRODUCTION COSTS AND ADDITIONAL VALUE OF GROWTH UNIT AND ORGANIC RICE MANUFACTURER OF INDEPENDENT ORGANIC RICE I IN THE VILLAGE OF LOMBOK KULON KECAMATAN WONOSARI BONDOWOSO DISTRICT - Syahputri, Indira Rosandry Ajeng; Hapsari, Triana Dewi; Kuntadi, Ebban Bagus (Universitas Muhammadiyah Jember, 2019)
Organic Rice Processing and Production Unit of Tani Mandiri I is downstream agroindustry that produces organic rice to support organic rice farming in Lombok Village, Kulon. The research objective was to find out: (1) the production system (2) the efficiency of rice production costs and (3) the value of the added grain. The method used is a descriptive and analytical method. The sampling method uses purposive sampling. Data collection uses observation, structured interviews, and documentation studies. The results showed that (1) the procurement of raw materials had fulfilled the quantity and continuity aspects but had not fulfilled the quality aspect, the type of production applied by the intermittent type with the layout based on the process flow, the rice production process was not in accordance with the SOP at the drying, grinding, and sorting. (2) The use of rice production costs has been efficient with an efficiency value of 1.20. (3) Value-added Processing of GKP into GKG and GKG into packaged rice is positive, with the added value of IDR 40.73 per kg GKP and Rp 770.42 per kg GKG.